Seed germination and seedling physiology of ajowan (Trachyspermum ammi L.) under chloride salinity - K N Dhumal, R Yogita, T D Nikam, (Journal of Spices and Aromatic Crops, 2014)
Seed germination and seedling physiology of ajowan (Trachyspermum ammi) was investigated under salinity induced by NaCl. Five different salinity levels (0, 25, 50, 100 and 150 mM) were used. The results revealed that seed germination and seedling growth were significantly retarded due to salinity. Significant accumulation of various osmolytes like reducing sugars and total sugars, proline, glycine betaine and total free amino acids was recorded with increasing salinity. The reduction in protein and starch content of seedlings under stress condition was concentration dependent. The studies suggested that ajowan is moderately tolerant to salt stress at seed germination stage.